ANALISA PERANCANGAN SISTEM INFORMASI PENGHITUNGAN NILAI ASET PADA POLITEKNIK LP3I JAKARTA KAMPUS KRAMAT - Nasril, Nasril; Hanafi, Iqbal (POLITEKNIK LP3I JAKARTA, 2021)
Information system is the one example of technology products that are developing at this time. Information system can be used to help our activity, and to arrange humans live and process decision making. Polytechnic LP3I Jakarta Campus Keramat is one of the Universities that requires the participation of information technology to process the value of depreciation of assets owned, therefore an information system is designed that aims to meet those needs. Information System Design The calculation of asset values is designed using the straight-line method. And using the Use Case design model, Sequence diagram, Class Diagram, Activity Diagram and ERD. For applications on programs using PHP, as well as CodeIgnitor and XAMPP applications. The conclusion obtained in the Information System Design calculating the value of this asset is to provide convenience to the procedure for calculating the value of the assets. Keywords : Calculation of asset value, Use Case design model, Sequence diagram, Class Diagram, Activity Diagram and ERD